Governance and Firm Performance: An Expository Analysis of Listed Firms at Pakistan Stock Exchange - Shahid, Tayyab Zeeshan; Naz, Farah; Sehar, Sana; Hassan, Sarfraz; Butt, Ahsan (International Journal of Economics and Financial Issues, 2020)
This paper primarily focuses upon the adoptability of set of governance mechanisms evolved by the Securities and Exchange Commission of Pakistan (SECP) by the listed firms at Pakistan Stock Exchange (PSX). Purposefully, one of the heavily contributing industries of Pakistan, textile spinning industry has been targeted. Empirical estimation underwent the data of listed firms at PSX for the period of 2010-2018. Sources of the data were annually audited financial statements published by firms, Balance Sheet Analysis (BSA) and Financial Statement Analysis (FSA) published by the State Bank of Pakistan (SBP). Descriptive analytical reasoning along with panel data methodological adaptations including location and time fixed effects were conducted. Conclusions drawn upon the basis of estimation deduced that governance mechanisms carved by SECP, influenced the performances of listed firms positively and significantly. Keywords: Corporate Governance, Pakistan Stock Exchange, Performance, Textile Spinning Firms JEL Classifications: G30, G34, L20, L25 DOI: https://doi.org/10.32479/ijefi.9916